Gastroprotective Value of Berries: Evidences from Methanolic Extracts of Morus nigra and Rubus niveus Fruits - Luciane Angela Nottar Nesello; Maria Luisa Maes Lima Beleza; Marihá Mariot; Luísa Nathália Bolda Mariano; Priscila de Souza; Adriana Campos; Valdir Cechinel-Filho; Sérgio Faloni Andrade; Luísa Mota da Silva (Gastroenterology Research and Practice)
This study evaluated the gastroprotective value of the methanol extracts from fruits of Morus nigra L. (black mulberry (MEMN)) and Rubus niveus Thunb (raspberry (MERN)). The total phenolic compounds and flavonoids were measured, as well as the in vitro 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenger activity. The gastroprotective effects of the extracts against 60% ethanol/0.3 M HCl were evaluated in mice. After that, the lipid hydroperoxides and reduced glutathione levels at ulcerated tissue were determined. The effects of extracts on H+/K+-ATPase activity were also verified. The extracts exhibited high contents of polyphenols; however, MERN presented 1.5-fold higher levels. The presence of flavonoids also was confirmed. In addition, MEMN (IC50 = 13.74 μg/mL) and MERN (IC50 = 14.97 μg/mL) scavenged DPPH radical. The MEMN reduced the ulcer area only at 300 mg/kg (p.o.) by 64.06%. Interestingly, MERN decreased the ulcer area in a superior potency (ED50 = 20.88 mg/kg), reducing the ulcer area by 81.86% at 300 mg/kg, and increased the gastric mucin levels. The antioxidant effects of extracts were evidenced by reduced lipoperoxides and increased reduction of glutathione amount in the gastric mucosa. However, MEMN or MERN did not change the H+/K+-ATPase activity. These results confirm that M. nigra and R. niveus are berries with a gastroprotective value by strengthening of gastric protective factors.